Eksistensi Mahkamah Partai Politik dalam Menyelesaikan Perselisihan Internal Partai Politik - Pattiapon, Kristo Roland (Universitas Negeri Malang, 2020)
The purpose of this study was to analyze the existence of political party courts in resolving internal political party disputes under the provisions of Law Number 2 of 2011 concerning Amendments to Political Party Laws. This study used a juridical-normative method with a statute approach. The results of the study indicated that the mechanism for resolving internal political party disputes was carried out through political party courts. If the settlement through the political party court mechanism could not be reached, the settlement of political party disputes was carried out through the district court and could be continued with the submission of an appeal to the Supreme Court. The existence of the political party court in resolving political party disputes was evident in the authority of the political party court in regulating, managing and deciding internal political party problems with the power of decisions that were final and internally binding.